Gender and Sexual Relation in Pluto : A Story, a Planet, and Love Novel - Kansuwan, Siriyakorn (Journal of Buddhist Education and Research (JBER), 2025)
This research aims to analyze the gender roles of femininity and masculinity of the main characters in the novel Pluto: A Story, a Planet, and Love, as well as to examine the sexual relationships of the main characters in the same novel. It is a qualitative documentary research presented through descriptive analysis. The research frameworks employed include Doyle’s (1991) concept of femininity and masculinity, and Jackson and Scott’s (1996) theory of sexuality. The findings reveal two key aspects of femininity: attention to physical appearance and being an ideal or accomplished woman. In contrast, three aspects of masculinity are identified: 1) rejection of femininity, 2) the necessity of achieving success, and 3) the expression of aggression. Regarding the sexual relationships of the characters, five characteristics are found: 1. Sexual preferences; 2. Sexual desires; 3. Sexual practices; 4. Discourses that create opportunities for sexual encounters; 5. Sexual attitudes, which can be categorized into two perspectives: a conservative perspective and a modern perspective.